ANALISIS KOMPETENSI AKUNTANSI MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS LAMPUNG - Pujiati Pujiati (Metafora: Education, Social Sciences and Humanities Journal, 2020)
Analysis of Accounting Competence Education Student of Economics, University of Lampung. This study aims to: 1) analyze the economics of education student accounting competence FKIP Lampung University; 2) examine the factors that influence student mastery of accounting competence FKIP economic education Lampung University. This research is descriptive research subjects consisted of accounting faculty and 188 students were determined by proportional random sampling of the workforce 2012 until 2014. The data was collected through tests, observations, questionnaires, documentation, and interviews. The results showed that 1) the competence of accounting students are in either category for sub competence of recording financial transactions, whereas for sub competence of recapitulate are in enough categories, and in financial reporting sub-competencies are in either category. 2) Factors affecting the accounting competence is the ability to think critically, feedback and reinforcement of lecturers.